Philosophical And Pedagogical Documents of Legal Culture Development at Young People - G.N.Pirnazarov (Genius Journals, 2022)
This article discusses the role and socio-pedagogical features of the decree "On radical improvement of the system of raising legal awareness and legal culture in society" in raising the legal culture of
Keywords: legal culture,; students,